Casamento e compadrios: formação familiar escrava e forra na freguesia de Quixeramobim – Ceará (1740-1810) - Miranda, Luzia Leila Velez de (2018)
From the analysis of the ecclesiastical documentation of baptisms and marriages, this study investigates the social dynamics and the constitution of the family arrangements of enslaved subjects and linings in the Quixeramobim Freguesia, Ceará, between the years 1740 and 1810. The problematization of nuptials and births from the themes of naturalness, legitimacy, compadrio, legal conditions (free, enslaved and forra) and qualities (white, brown, black, indian, goat, etc.), allowed us to understand Quixeramobinense family everyday within the limits and possibilities of the slave system. For this, we take as theoretical-methodological north the postulates of Social History and Historical Demography. The analysis of selected social categories allowed us to understand how the constitutions of social networks of sociabilities and solidarities expressed through compadrio and unions considered "legitimate" (legitimized by the Catholic rite of marriage), consensuals, concubinates, consenting sexual relations, or rapes that came to bear children (perceived through the natural children present in the baptismal records). In the same way, from the observation of these relations, we approached the questions involving the dynamics of the worlds of free and slave labor in the space and time of the Quixeramobim Freguesia.